A Bibliometric Study of Green Finance Research in 2000 until 2024 - Judijanto, Loso (Westscience Press, 2025)
This bibliometric study explores the evolution of green finance research from 2000 to 2024, employing a comprehensive dataset derived from Scopus. It analyzes the development of themes, the geographic distribution of research, and the dynamics of academic collaboration within the field. Our findings indicate a significant growth in literature, with a pronounced focus on sustainable investments, green bonds, and the integration of environmental concerns into banking practices. The study highlights the role of technological innovation and decentralized finance in advancing the field, reflecting a shift towards more efficient and transparent financial processes. Geographical analysis reveals a strong contribution from countries like China, India, and the United States, with extensive international collaborations across continents. The research landscape is characterized by a diverse array of contributions that address both the economic and environmental aspects of green finance. This study provides valuable insights into the intellectual structure of green finance and suggests areas for future research, including the need for more interdisciplinary approaches and empirical studies to assess the effectiveness of green finance mechanisms.